Manajemen Kepala Sekolah dalam Menanamkan Budaya Islami Melalui Pendidikan Model Full Day School Studi Kasus di SD Islam Nabawi Kedungadem - Angga Prastiyo; Nadia Arifia (Mudir : Jurnal Manajemen Pendidikan, 2021)
Education is absolute in life, both in the life of a person and family, as well as in the life of the nation and state. So that life is very important and cannot be separated from life, because the progress of a nation and state is largely determined by the educational progress of the nation or country. Given the very importance in life, so education must be implemented. in order to obtain the desired result. The cultivation of Islamic culture is one of the policies that must be considered by schools in general or Islamic educational institutions in particular. With the existence of Islamic culture in schools or Islamic educational institutions can introduce and instill Islamic religious values ​​so that in the process of child development later they will always hold fast to the values ​​of Islamic teachings and can form the moral character of students, besides that they can realize the values ​​of Islam. religious teachings as a tradition that must be applied by Islamic educational institutions. Principals who are able to develop Islamic culture in schools, namely by using the strategies they have to develop Islamic culture in schools by using full day school education models